2018
DOI: 10.1088/1748-9326/aaaad1
|View full text |Cite
|
Sign up to set email alerts
|

The impact of land ownership, firefighting, and reserve status on fire probability in California

Abstract: The extent of wildfires in the western United States is increasing, but how land ownership, firefighting, and reserve status influence fire probability is unclear. California serves as a unique natural experiment to estimate the impact of these factors, as ownership is split equally between federal and non-federal landowners; there is a relatively large proportion of reserved lands where extractive uses are prohibited and fire suppression is limited; and land ownership and firefighting responsibility are purpo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
41
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(41 citation statements)
references
References 60 publications
0
41
0
Order By: Relevance
“…Nonparametric models may be helpful as they allow conditional fire probability to vary with factors such as tree density and land ownership (e.g. Wilson et al, 2010;Starrs et al, 2018).…”
Section: Criticisms and Research Questionsmentioning
confidence: 99%
“…Nonparametric models may be helpful as they allow conditional fire probability to vary with factors such as tree density and land ownership (e.g. Wilson et al, 2010;Starrs et al, 2018).…”
Section: Criticisms and Research Questionsmentioning
confidence: 99%
“…Risk of reversal from wildfires was considered for conservation scenarios because severe fire seasons burned more than 2.5 Mha in British Columbia in 2017 and 2018 [54], and reserve status has been linked to wildfire probability in other regions [52]. Future severe fire seasons are expected for the interior and southern Cordillera of western Canada due to increasing temperatures [19,63], high fuel loads from Mountain Pine Beetle after-effects [62], and reduced fuel moisture from changing weather patterns [64].…”
Section: Discussionmentioning
confidence: 99%
“…Managers cannot be certain that a wildfire will occur within the expected lifespan of a fuel treatment, so the probability of a wildfire occurring is an important factor to consider when attempting to predict the net carbon impact of fuel treatments (Finney 2005, Hurteau et al 2009, Campbell et al 2012, Krofcheck et al 2018). Starrs et al (2018) found annual wildfire probabilities in California forests ranging from 0.005 to 0.025 during the years 2000–2015. However, the probability of treatment–wildfire interactions is likely to increase as large wildfires become more frequent as climate is expected to be more conducive for wildfire spread (Westerling et al 2011, Collins 2014).…”
Section: Discussionmentioning
confidence: 99%
“…By using actual conditions from nearby wildfires that posed substantial fire control problems, we believe predicted fire behavior may better characterize wildfire potential, as opposed to using conditions based on fire‐weather percentile thresholds. The vast majority of area burned by wildfires in California is burned by large fires, and it is reasonable to assume that if a treated area does experience a wildfire, it will likely be under intense weather conditions (Starrs et al 2018).…”
Section: Methodsmentioning
confidence: 99%